„Bez Ducha svatého nemůže být ani křesťanství, jen víra v tradici.“: Etnografická studie letničního a neocharismatického společenství v současné ČR - Soukupová, Monika (Lidé města, 2017)
This article focuses on the Pentecostal and Charismatic movements as part of Evangelical Christianity in contemporary Czech Republic. The text is a resumé of ethnographic research conducted in two Czech Pentecostal Churches – the Apostolic Church in Prague and the Christian Fellowship Church. In these communities, certain aspects of Pentecostal church life were observed using the participant observation method, as well as interviews with informants. The aim of the research was to focus on how these believers understand Pentecostal religiosity, and where we can see some crucial aspects of this kind of religiosity within church activities. I try to explain why the home groups and community prayer are more important for my informants than large-scale impersonal activities. Further attention was focused on the preferred forms of evangelization. I want to demonstrate the shift from mass evangelization in the 1990s to the current personal form of evangelization, based on deep personal relationships with unbelievers.